2021
DOI: 10.48550/arxiv.2101.11089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chatbots language design: the influence of language variation on user experience

Abstract: Chatbots are often designed to mimic social roles attributed to humans. However, little is known about the impact on user's perceptions of using language that fails to conform to the associated social role. Our research draws on sociolinguistic theory to investigate how a chatbot's language choices can adhere to the expected social role the agent performs within a given context. In doing so, we seek to understand whether chatbots design should account for linguistic register. This research analyzes how registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In this position paper, we argue that register analysis should be used as a technique for providing a theoretical basis for chatbot language design, grounded on the results presented in Chaves et al [6]. To design register-specific language for chatbots, we need to enrich chatbots with computational models that can adapt the utterances to conform with the expected register, in an effort to mimic the subconscious humans' language production process.…”
Section: Implications For Chatbot Designmentioning
confidence: 99%
See 3 more Smart Citations
“…In this position paper, we argue that register analysis should be used as a technique for providing a theoretical basis for chatbot language design, grounded on the results presented in Chaves et al [6]. To design register-specific language for chatbots, we need to enrich chatbots with computational models that can adapt the utterances to conform with the expected register, in an effort to mimic the subconscious humans' language production process.…”
Section: Implications For Chatbot Designmentioning
confidence: 99%
“…Previous studies have found that appropriate language style is not relevant for determining user satisfaction as long as the user can understand the chatbot's answer, only advising that the chatbot's language style should be "mildly appropriate to the service the chatbot provides" [1]. In a previous study [6], however, we found evidence that user experience goes beyond merely comprehending a chatbot's utterance to whether the user perceives the chatbot's language as appropriate and credible. In that study, we explored the applicability of register to human-chatbot interactions by developing a rationale for accounting for register in chatbot design, and providing a mechanism for implementing theory into design practice.…”
Section: Register For Chatbot Language Designmentioning
confidence: 99%
See 2 more Smart Citations